2005
DOI: 10.1007/s00424-005-1499-y
|View full text |Cite
|
Sign up to set email alerts
|

Impaired ability to increase water excretion in mice lacking the taurine transporter gene TAUT

Abstract: Cellular taurine uptake or release counteracts alterations of cell volume. Na+-coupled taurine transporter TAUT mediates concentrative cellular uptake of taurine. Inhibition of vasopressin secretion by hypotonicity may involve taurine release from glial cells of supraoptic nucleus. We compared renal function of mice lacking TAUT (taut-/-) and wild-type littermates (taut+/+). We observed renal taurine loss and subsequent hypotaurinemia in taut-/- mice. With free access to water, plasma and urine osmolality, uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Marked increases in urine output and free-water clearance in response to glycine in the PVN suggest that this neurotransmitter may have an inhibitory influence on magnocellular neuronal activity and the release of AVP into the systemic circulation. This possibility is also suggested by the observation that taurine, which has affinity for glycine receptors, has an inhibitory influence on rat SON magnocellular neurons in vitro (Hussy et al, 2000) and in vivo (Huang et al, 2006). In accordance with this premise, we demonstrated that lowdose intravenous AVP infusion prevented the diuretic (and natriuretic) response to microinjection of glycine into the PVN.…”
Section: Discussionsupporting
confidence: 86%
“…Marked increases in urine output and free-water clearance in response to glycine in the PVN suggest that this neurotransmitter may have an inhibitory influence on magnocellular neuronal activity and the release of AVP into the systemic circulation. This possibility is also suggested by the observation that taurine, which has affinity for glycine receptors, has an inhibitory influence on rat SON magnocellular neurons in vitro (Hussy et al, 2000) and in vivo (Huang et al, 2006). In accordance with this premise, we demonstrated that lowdose intravenous AVP infusion prevented the diuretic (and natriuretic) response to microinjection of glycine into the PVN.…”
Section: Discussionsupporting
confidence: 86%
“…To the best of our knowledge, there are no genetically modified mice with such an antidiuresis phenotype at baseline. An impaired ability to lower urine osmolality and increase urinary water excretion was recently reported in mice that lack the taurine transporter gene Taut (57), which could play a role in primary cilia (58). Thus, in addition to the interactions between polycystins and calcium signaling pathways, the Pkd1 ϩ/Ϫ mice could give insights into the mechanisms that govern osmoregulation, AVP signaling, and trafficking of AQP2 in the CD.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the high quality of the spectra, we conclude here that the gastric isoform is expressed in the rat IMCD, although this identification does not exclude the presence of the colonic isoform as well. TauT, a sodium-and chloride-dependent taurine transporter, is an interesting protein because mice lacking TauT have impaired ability to increase water excretion in response to water loading (36). Another potential apical membrane marker protein is the GPI-linked membrane protein lipoprotein lipase (Table II).…”
Section: Discussionmentioning
confidence: 99%